(untitled) (Research, Society and Development, 2022)
Propolis is a natural resinous mixture produced by bees from substances collected from plant parts, shoots and exudates. Due to its waxy nature and mechanical properties, bees use propolis in the construction and repair of their hives and this substance is widely known to have a beneficial effect on human health, including wound healing. In this context, this research aimed to approach, through a systematic review, the use of propolis extract in the clinic of lesions and wound healing in the skin, taking into account its benefits. The research consisted of a systematic review, with a quantitative approach, which used the descriptors “Propolis” OR “Apis mellifera L.” and “Wound Healing”, also applying the time interval of the last five years. For data collection, the aforementioned inclusion and exclusion criteria were used. When using the descriptors and time interval in the three databases, a total of 378 articles was found, which after a filtering process using the inclusion and exclusion criteria mentioned above, a final result of eleven articles were selected. The studies demonstrated in this research present the propolis extract as a promising treatment in the healing of the skin, taking into account the therapeutic effect of its constituents that, in an effective way, accelerates the tissue repair process, significantly improving the quality of life for patients with lesions.